Green fluorescent protein based pH indicators for in vivo use: a review - Bizzarri, Ranieri; Serresi, Michela; Luin, Stefano; Beltram, Fabio (Analytical and bioanalytical chemistry, 2009)
Green fluorescent protein (GFP) and its variants have been used as fluorescent reporters in a variety of applications for monitoring dynamic processes in cells and organisms, including gene expression, protein localization, and intracellular dynamics. GFP fluorescence is stable, species-independent, and can be monitored noninvasively in living cells by fluorescence microscopy, flow cytometry, or macroscopic imaging techniques. Owing to the presence of a phenol group on the chromophore, most GFP variants display pH-sensitive absorption and fluorescence bands. Such behavior has been exploited to genetically engineer encodable pH indicators for studies of pH regulation within specific intracellular compartments that cannot be probed using conventional pH-sensitive dyes. These pH indicators contributed to shedding light on a number of cell functions for which intracellular pH is an important modulator. In this review we discuss the photophysical properties that make GFPs so special as pH indicators for in vivo use and we describe the probes that are utilized most by the scientific community.